KAJIAN SISTEM AGRIBISNIS UBI KAYU PADA KELOMPOK TANI SUNGAI SUCI DI DESA PASAR PEDATI KECAMATAN PONDOK KELAPA KABUPATEN BENGKULU TENGAH - Siallagan, Yesco Christmas; Asriani, Putri Suci; Andani, Apri (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2016)
The purpose of this study are identifying the types and the role of the subsystems of production facilities in the agribusiness system cassava managed by Farmer Group of Sungai Suci, subsystem farming analyzed in agribusiness system cassava managed by Farmers Group in Sungai Suci, analyze subsystem agroindustry in the agribusiness system managed by Farmer Group in Sungai Suci, analyze marketing subsystem in cassava agribusiness system managed by Farmers Group in Sungai Suci, identifying the types and subsystems supporting role in the system of cassava agribusiness managed by Farmer Group in Sungai Suci.The determination location methode is purposive. Respondents determination in this study using census methode in the Sungai Suci Farmer Group. Data collected was primary data and secondary data. Data were analyzed using descriptive analysis, farming analysis, agroindustry analysis, and marketing channels analysis.The result showed that Cassava farm incomes on average per ha in one growing season is the real income is Rp 18.681.033, unriil revenue is Rp 12.626.045 Cassava agroindustry every month have the income namely: from the farmers directly to agroindustrial Cassava Farmers Sungai Suci and from farmers to collectors village level and then to the consumer artisans cassava processing while the processed agroindustrial cassava there are three grooves, namely: mocaf flour processing Rp 1.707.500,- Rengginang Rp.1.650.693-, and Rp.2.513.400 chips. Flow marketing of cassava includes two strands, namely: from the farmers directly to agroindustrial Cassava Farmers Sungai Suci and from farmers to collectors village level and then to the consumer artisans cassava processing while the processed agroindustry cassava there are three grooves, namely: from farmer groups to consumers artisan cakes and households, the second from farmer groups to household consumers, and a third of farmers' groups to a merchant retailers and then to consumers. Subsystems supporting role in agribusiness systems of cassava in the Sungai Suci Farmers Group is Women Farmers Sungai Suci and the Government cooperation.